2021
DOI: 10.21037/jtd-20-2277
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical implications of estrogen receptors in thoracic malignancies: a narrative review

Abstract: Thoracic malignancies represent a significant global health burden with incidence and mortality increasing year by year. Thoracic cancer prognosis and treatment options depend on several factors, including the type and size of the tumor, its location, and the overall health status of patients. Gender represents an important prognostic variable in thoracic malignancies. One of the greatest biological differences between women and men is the presence of female sex hormones, and an increasing number of studies su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 103 publications
(93 reference statements)
1
10
0
Order By: Relevance
“…The gender-specific biological and clinical features of lung cancer have been described previously [29,30], suggesting that lung cancer in women and men are distinct entities, mainly because of the involvement of genetic alterations and hormonal factors. Rouquetta et al [3] observed a higher rate of EGFR mutations in women. ER and EGFR were also expressed more frequently in women and there was a positive link between the expression of EGFR and of ER.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The gender-specific biological and clinical features of lung cancer have been described previously [29,30], suggesting that lung cancer in women and men are distinct entities, mainly because of the involvement of genetic alterations and hormonal factors. Rouquetta et al [3] observed a higher rate of EGFR mutations in women. ER and EGFR were also expressed more frequently in women and there was a positive link between the expression of EGFR and of ER.…”
Section: Discussionmentioning
confidence: 97%
“…Unfortunately, due to the lack of efficient diagnostic methods, early detection of cancer, when currently available treatment schemes are most effective, is rare. The development of lung cancer is a multi-annual and multi-stage process that could be initiated by several carcinogens, as well as by hormonal and genetic features [2,3]. However, too little is still known about host factors facilitating the initiation and progression of tumor development and determining the individual response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The possible mechanisms of difference between males and females were as follows: First, the comorbidity score in males was higher than that in females ( 23 ); however, there was no related data in the SEER database. Second, estrogen receptors (ERs) are highly expressed in ESCC, and estrogens were confirmed to inhibit squamous cell tumor growth ( 24 , 25 ). Third, oncogenic types of HPV have been proved to play an important role in ESCC in high-risk areas ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Malignant pleural mesothelioma (MPM) is a rare (prevalence 8–30 cases/million/year) and aggressive neoplasm, originating from the mesothelium lining the pleural surface of the lungs [ 1 ], which has been largely attributed to environmental/occupational exposure to asbestos fibers (83% of cases) [ 2 , 3 ]. However, despite the ban of using asbestos in many countries for over 20 years, the incidence of MPM has failed to decline worldwide, with a total of 250,000 deaths anticipated for the next 30 years [ 4 , 5 ] because of the following reasons: (i) a significant lag between first-time exposure to asbestos and the onset of symptoms in an aging, genetically susceptible population (≥ 30–60 years) [ 6 , 7 ]; (ii) on-going use of asbestos in middle-income and low-income countries [ 8 ]; (iii) presence of other risk factors of MPM’s pathogenesis, including refractory ceramic fibers [ 9 ], hormonal factors [ 10 , 11 ], and some mineral (erionite, fluoro-edenite) or chemical exposures [ 12 15 ] such as ionizing radiation [ 16 18 ].…”
Section: Epidemiology and Clinic Of Malignant Pleural Mesothelioma (Mpm)mentioning
confidence: 99%